The Dual/Global Value of SARS-CoV-2 Genome Surveillance on Migrants Arriving to Europe via the Mediterranean Routes - Marotta, Claudia (Ann Glob Health, 2021)
Despite the pandemic, 34,154 migrants, refugees or asylum-seekers landed in Sicily (Italy) in 2020, representing the main point of entry by sea into Europe. The SARS-CoV-2 surveillance program among migrants arriving to Sicily via the Mediterranean Sea, made by the combination of clinical examination and molecular testing, has been integrated by full-genome sequencing strains using the NGS technology from the last week of February. To date, more than one hundred full-genome strains have been sequenced and 8 different lineages have been identified mostly belonging to the lineages B.1.1.7 and B.1.525. As global access to COVID-19 vaccines should be ensured, the need to provide more detailed information to inform policies and to drive the possible re-engineering of vaccines needed to deal with the challenge of new and future variants should be highlighted.